(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Sustainability is of utmost importance in order to confront the threat of global climate change and water scarcity in most countries. For this reason, it has become necessary to treat and reuse gray water (water generated from sinks, kitchens, and washing machines), as it constitutes the largest portion of wastewater about 75% from wastewater[1] and is less polluted, to reduce consumption water.This study set out to understand the scientific underpinnings of gray water as well as the global advancements in the field of gray water treatment. To this end, it compiled a list of all the top journals and researchers worldwide, as well as the actual number of research papers published worldwide and the annual growth rate for the previous ten years. The literature and research on gray water treatment during the last 10 years was studied from (2014 to 2023) and reviewed, and the data was collected and downloaded in Excel format with a total of more than 891 research papers through the Dimension website, which lists the details of authors and researchers in all universities and countries, while monitoring joint cooperation and comprehensive scientific citations and displaying them with images and data through the program. Viewer VOS and with the help of the term (grey water treatment). The rate of rise in research over the past ten years has been roughly 82.2%. This indicates a significant increase in the importance of sustainability in general and gray water treatment in particular.